Hepatic Histopathology Among Excessive Drinkers Without Advanced Liver Disease. (26th March 2021) - Chang, Binxia; Huang, Ang; Saxena, Romil; Sun, Yin; Liu, Shuhong; Zhou, Guangde; Li, Baosen; Teng, Guangju; Zhao, Jun; Zhang, Wei; Jiang, Yanchao; Han, Sen; et al.
Abstract: Aims: Alcohol-associated liver disease represents a spectrum of histopathological changes from steatosis to advanced fibrosis and cirrhosis. The major goals of this retrospective study were to characterize the histologic features in patients with excessive alcohol use who presented with an abnormal hepatic panel and/or abnormal radiographic imaging and did not meet the clinical diagnosis of alcoholic hepatitis or cirrhosis. Methods: We performed a retrospective study to describe hepatic histology of 62 and 83 excessive drinkers with normal and abnormal serum aspartate transaminase, respectively. The types of inflammatory cells in the liver were characterized by immunohistochemistry for CD4, CD8, CD20, CD68 and myeloperoxidase. Results: Among 62 patients with aspartate aminotransferase (AST) ≤ 50 U/L, 37% had histological evidence of steatosis. Of these, we found evidence of hepatocyte ballooning (21%), lobular inflammation (50%), portal inflammation (52%) and fibrosis (14%). For those with AST > 50 U/L, the presence of hepatic steatosis, lobular inflammation and portal inflammation was observed in 29, 60 and 69% of patients, respectively. Fibrosis was found in 33%, four with bridging fibrosis, and one with cirrhosis. We observed the aggregation of CD68 + macrophages, rather than normally distributed with minimal neutrophilic infiltration. Lobular and portal lymphocytic infiltrations are primarily CD8 + T cells. Conclusion: Abnormal hepatic histopathology occurs in excessive drinkers with normal transaminase activity. Future studies to determine the diagnostic modalities to detect such abnormalities and to better understand its clinical implications and long-term outcome are needed.